2012
DOI: 10.5194/hess-16-1607-2012
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of soil parameters over bare agriculture areas from C-band polarimetric SAR data using neural networks

Abstract: Abstract. The purpose of this study was to develop an approach to estimate soil surface parameters from C-band polarimetric SAR data in the case of bare agricultural soils. An inversion technique based on multi-layer perceptron (MLP) neural networks was introduced. The neural networks were trained and validated on a noisy simulated dataset generated from the Integral Equation Model (IEM) on a wide range of surface roughness and soil moisture, as it is encountered in agricultural contexts for bare soils. The pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 42 publications
2
72
0
Order By: Relevance
“…In order to improve soil parameters estimates, a priori knowledge about soil moisture was introduced. Baghdadi et al [15] showed that the use of a priori knowledge on soil moisture (dry to slightly wet or very wet information) improves soil moisture estimates. The a priori information on the moisture volumetric content "mv" was provided by an expert when using meteorological data (precipitations, temperature).…”
Section: Methodological Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve soil parameters estimates, a priori knowledge about soil moisture was introduced. Baghdadi et al [15] showed that the use of a priori knowledge on soil moisture (dry to slightly wet or very wet information) improves soil moisture estimates. The a priori information on the moisture volumetric content "mv" was provided by an expert when using meteorological data (precipitations, temperature).…”
Section: Methodological Overviewmentioning
confidence: 99%
“…For each hidden layer, the number of neurons was determined by training the networks in order to obtain a good estimate of parameters while keeping a reasonable computing time. A number of 20 neurons was used [15]. For soil moisture estimation, two transfer functions were used, the first is Linear and the second is Tangent-Sigmoid.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…The variability of the predicted soil moisture on a given day is larger Figure 11. Distribution of the soil moisture within the Thau catchment for three different dates; (a) is the observed soil moisture (Baghdadi et al, 2012) and (b) is the predicted soil moisture based on the regionalization results. when this day is preceded by wet days (Table 7).…”
Section: Fit To Geographymentioning
confidence: 99%
“…Baghdadi et al (2012) proposed a method to estimate the volumetric soil moisture from RADARSAT-2 image (space Synthetic Aperture Radar "SAR" sensor) for bare agricultural fields or fields with thin vegetation cover over the Thau Basin for 10 dates between November 2010 and March 2011. Their estimated soil moisture values showed a good agreement with the measured in situ soil moisture, with RMSE = 0.065 cm 3 cm −3 (see Baghdadi et al, 2012 for details). These estimated soil moisture maps, referred to hereafter as observed soil moisture, are compared to the soil moisture derived from the regionalization results, which are referred to hereafter as predicted soil moisture.…”
Section: Fit To Geographymentioning
confidence: 99%
“…However, these estimations require the use of a radar backscattering model that is capable of correctly modeling the radar signal. The Integral Equation Model (IEM) [1,2] is widely used in inversion procedures of SAR images for retrieving soil moisture content and roughness (e.g., [3][4][5][6][7][8][9]). Its validity domain covers the range of surface roughness values (root mean square height "rms") encountered on agricultural soils (k.rms ≤ 3, where k is the wave number = 0.24 cm −1 for a frequency in L-band of 1.25 GHz).…”
Section: Introductionmentioning
confidence: 99%